2021
DOI: 10.3390/ijerph19010374
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acid Load, Serum Polychlorinated Biphenyl Levels, and Mortality Following Breast Cancer in the Long Island Breast Cancer Study Project

Abstract: Dietary acid load (DAL) may be associated with all-cause mortality (ACM) and breast cancer-specific mortality (BCM), and these associations may be modified by serum polychlorinated biphenyl (PCB) levels. Participants included 519 women diagnosed with first primary in situ or invasive breast cancer in 1996/1997 with available lipid-corrected PCB data. After a median of 17 years, there were 217 deaths (73 BCM). Potential renal acid load (PRAL) and net endogenous acid production (NEAP) scores calculated from a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The differences, however, were not statistically significant. DAL scores were positive throughout (> 0 mEq/d), and suggested that cancer survivors in general consumed an acidifying diet that has been associated with adverse effects in the existing studies in cancer survivors [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The differences, however, were not statistically significant. DAL scores were positive throughout (> 0 mEq/d), and suggested that cancer survivors in general consumed an acidifying diet that has been associated with adverse effects in the existing studies in cancer survivors [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…DAL scores in the range of 50 mEq/d to 60 mEq/d have been associated with adverse health effects and repercussions in analyses using data from the WHEL study in breast cancer survivors [ 27 30 ]. Comparable PRAL and NEAP scores have also been associated with an increased mortality in breast cancer survivors [ 27 ], and may contribute to reduced overall physical health [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diets with high intakes of protein (e.g., meat) and low intakes of fruit and vegetables are acid-producing diets. Our group has shown that breast cancer survivors are susceptible to acid-producing diets, resulting in an increased risk of mortality, depression, and reduced physical function [ 20 , 21 , 22 , 23 ]. Cancer survivors have a lower capacity to adjust acid-base balance than the general population [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%